Investment in research and development and macroeconomic fluctuations: a general equilibrium model for a small open economy - Sanchez Tapia, William Richard (2023)
A model of Real Business Cycles that includes a sector that generates Research and Development (R&D) at the product level is estimated in order to assess the quantitative importance of this sector in the macroeconomic dynamics of a small and open economy like the Peruvian economy. It is found that an efficiently innovative product-level sector plays a crucial role as a "shield" for the economy against exogenous shocks and amplifies macroeconomic dynamics in the face of R&D policies. Thus, the R&D sector manages mitigates the initial impact on economic growth arising from an adverse internal shock by 0.6 percentage points, and from an unfavorable external shock by 2 percentage points compared to the scenario without an R&D sector. Likewise, a 1 percent increase in innovation at the product level (more varieties of products in the economy) rises GDP growth by 0.35 percentage points, boosts employment growth by 0.20 percentage points, and increases the growth of the economy's productivity by 0.90 percentage points.